Comparison of Effect of Phenytoin and Levetiracetam in Neonatal Seizures - Tabassum, Arshia; Rafique `, Arshad; Qadir , Wahab; Shahzad, Muhammad Shoail; Fakhar Ul Zaman, Muhammad; Sohail, Azka (Journal of Fatima Jinnah Medical University, 2024)
Background: Neonatal seizures occur in the first 28 days of life and are a major threat to the neonate’s developmental outcome. Phenytoin and levetiracetam are both drugs available as treatment options for neonatal seizures. The objective of this study was to compare the effectiveness of standard recommended doses of phenytoin and levetiracetam in terms of treatment, duration of control, and prevention of recurrence of neonatal seizures at follow-up. Patients and methods: A randomized controlled trial was conducted in the NICU Department of Central Park Teaching Hospital, Lahore, from 15 February 2022 till 14 February 2023. The study included 80 neonates divided into two groups, Group A and B, having 40 neonates in each. The efficacy of both drugs was compared across these groups. T-test was performed on SPSS and a p-value of less than 0.05 was considered as significant. Results: There was a significant difference in neonatal seizure control of both the groups of 40 neonates in each group during the hospital stay as well as on 7 days follow up with Levetiracetam being more effective. Conclusion: Levetiracetam was more effective in comparison with phenytoin in the management of neonatal seizures.